Immunologic Quality Improvement of Racing Pigeon Squabs through Induction of Cropmilk using Probiotic Lactobacillus sp. - Irianto, Agus; Budiyanto, B Heru (ANIMAL PRODUCTION, 2004)
Probiotic is live microbial cells supplementation that has beneficial effect to the host. Feeding adult pigeons (Columba livia) with food supplemented with probiotic, Lactobacillus sp., at concentration 106,108, and 1010 cells g-1 respectively have been done in order to improve the immunologic quality of the squabs. Immunologic response namely the number and activity of kidneyâs macrophage were examined. Also, the pathologic signs which developed following artificial infection by intramuscular injection with Escherichia coli suspension was examined. The result indicated that adult pigeon feed with food containing probiotic have beneficial effect to the squabs (through cropmilk) by improving their immune response namely increasing the number of kidneyâs macrophage and their in vitro phagocytic activity. Also, it reduced the E. coli population in the squabsâ gut. (Animal Production 6(2): 11-124 (2004)Â Key Words: pigeon squab, probiotic, Lactobacillus sp., immune response